A closed-loop EKF and multi-failure diagnosis approach for cooperative GNSS positioning - Liu, Haiying; Meng, Xiaolin; Chen, Zhiming; Stephenson, Scott; Peltola, Pekka (Springer Verlag, 2016)
Current cooperative positioning with Global Navigation Satellite System (GNSS) for connected vehicle application mainly uses pseudorange measurements. However the positioning accuracy offered cannot meet the requirements for lane-level positioning, collision avoidance and future automatic driving, which needs real-time positioning accuracy of better than 0.5m. Furthermore, there is an apparent lack of research into the integrity issue for these new applications under emerging driverless vehicle applications. In order to overcome those problems, a new Extended Kalman Filter (EKF) and a multi-failure diagnosis algorithm are developed to process both GNSS pseudorange and carrier phase measurements. We first introduce a new closed-loop EKF with partial ambiguity resolution (PAR) as feedback to address the low accuracy issue. Then a multi-failure diagnosis algorithm is proposed to improve integrity and reliability. The core of this new algorithm includes using Carrier phase based Receiver Autonomous Integrity Monitoring (CRAIM) method for failure detection, and the double extended w-test detectors to identify failure. A cooperative positioning experiment was carried out to validate the proposed method. The results show that the proposed closed-loop EKF can provide highly accurate positioning, and the multi-failure diagnosis method is effective in detecting and identifying failures for both code and carrier phase measurements.